PENGARUH PENGGUNAAN SPOILER PADA MOBIL BOX TERHADAP KOEFISIEN DRAG - Rendi, Rendi; Firman, Muhammad; Mujiburrahman, Mujiburrahman; Irawan, Heri (Universitas Lambung Mangkurat, 2024)
This research aims to investigate the effect of spoiler usage on box trucks on the coefficient of drag. A high coefficient of drag on box trucks can result in inefficient fuel consumption and higher exhaust gas emissions. Spoilers are installed on the top of the box truck to help streamline airflow and reduce air pressure above the vehicle, thereby reducing air resistance and improving vehicle performance. Although spoilers on box trucks have been used in the logistics and transportation industry, their effect on the coefficient of drag has not been extensively studied. Therefore, this research is expected to provide information to optimize vehicle performance and reduce the negative impact of vehicles on the environment.